A Review of Existing Microgrid Architectures - Lubna Mariam; Malabika Basu; Michael F. Conlon (Journal of Engineering)
The future electricity network must be flexible, accessible, reliable, and economic according to the worldwide smartgrid initiative. This is also echoed by the Sustainable Energy Authority of Ireland (SEAI) and European Electricity Grid Initiative (EEGI). In order to facilitate these objectives and to reduce green house gas (GHG) emission, research on various configurations of microgrid (μG) system is gaining importance, particularly with high penetration of renewable energy sources. Depending on the resource availability, geographical locations, load demand, and existing electrical transmission and distribution system, μG can be either connected to the grid or can work in an autonomous mode. Storage can also be a part of the μG architecture. This paper presents a critical literature review of various μG architectures. The benefits of grid-connected or isolated μG with storage have also been identified.